Fabrication of 15NV-centers in diamond using a deterministic single ion implanter - Groot-Berning, Karin; Jacob, Georg; Osterkamp, Christian; Jelezko, Fedor; Schmidt-Kaler, Ferdinand (New Journal of Physics, 2021)
Nitrogen vacancy (NV) centers in diamond are a platform for several important quantum technologies, including sensing, communication and elementary quantum processors. In this letter we demonstrate the creation of NV centers by implantation using a deterministic single ion source. For this we sympathetically laser-cool single molecular ions in a Paul trap and extract them at an energy of 5.9 keV. Subsequently the ions are focused with a lateral resolution of 121(35) nm and are implanted into a diamond substrate without any spatial filtering by apertures or masks. After high-temperature annealing, we detect the NV centers in a confocal microscope and determine a conversion efficiency of about 0.6%. The 15NV centers are characterized by optically detected magnetic resonance on the hyperfine transition and coherence time.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Deterministic implantation; Nv creations; Single ion implantation